Observations of Microwave Emission from Solar Jets and Comparison with Magnetohydrodynamic Simulations - Costas E. Alissandrakis; Vasilis Archontis; Kostas Moraitis (The Astrophysical Journal)
We computed the thermal microwave emission from a 3D magnetohydrodynamic (MHD) simulation and compared it with observations of solar jets. The simulation treats the emergence of magnetic flux into the solar atmosphere and its interaction with a low, preexisting ambient magnetic field. This interaction leads to the formation and development of a jet, driven by an eruption. The computed 17 GHz radio emission is compared with a number of observed jets, with respect to their morphology, their flux, and the rise time of the radio flux. We find that the MHD model reproduces the characteristics of lower-intensity jets reasonably well, whereas there are differences with stronger jets. We suggest possible ways to obtain more realistic jets from MHD simulations, so that they better match the real jets.